Broadly neutralizing monoclonal antibodies against influenza A viruses: current insights and future directions - Mahrous, Nahed N.; Alhumaidan, Ohoud S.; Alkhoshaiban, Abdulaziz S.; Tafish, Rawan T.; Al-Ghnnam, Fatimah F.; Althubyani, Maha; Al-Hubaysh, Abeer; Jamous, Yahya F. (Frontiers in Microbiology, 2026)
Monoclonal antibodies (mAbs) have become attractive tools for both the treatment and prevention of influenza A viruses due to their ability to target several viral components, which confers broad therapeutic potential. Advances in biotechnology, such as hybridoma technology, phage display technology, B cell immortalization, and artificial intelligence (Al)-driven antibody design, have significantly accelerated the development of effective mAbs. Clinical trials have shown that mAbs can improve clinical outcomes particularly in high-risk and immunocompromised populations by lowering viral loads and reducing disease severity. However, high production costs, the need for intravenous administration, and the risk of viral escape mutations are some of the obstacles to widespread clinical adoption. Post-marketing surveillance serves as a valuable source of information regarding safety, real-world effectiveness, and patterns of resistance. Broadly neutralizing antibodies (bnAbs), particularly those directed against conserved regions of the virus’s surface proteins, such as hemagglutinin (HA) and neuraminidase (NA), have demonstrated efficacy against antigenic drift-derived variants. Nevertheless, the emergence of escape mutants underscores the need for careful monitoring of mAb candidates and combination therapy. Monitoring genomic shifts requires a careful focus on the targeted regions affected by combination therapy. Challenges in accessibility are compounded by financial barriers, emphasizing the importance of large-scale production and alternative delivery methods, such as inhaled mAbs. To ensure that future mAb-based therapies for influenza A are both effective and accessible, it is critical to integrate resistance surveillance tools, monitoring AI, and advanced computational modeling in therapeutic strategies. This comprehensive review discusses the potential of mAbs to enhance influenza A treatment by offering precise and adaptable alternatives to traditional antivirals. It also examines recent technological advances, clinical performance, and scalability that may redefine future therapeutic strategies.